An Optimization-based Approach for design Ion Exchange Treatment Unit - Hamza, Zohul A. Hadi (Basrah Journal for Engineering Sciences, 2014)
The objective function is to satisfy certain constraints and achieve minimum capital, maintenance, and operation costs. Ion exchange unit was used in this study. This study includes development of computer program for advanced wastewater treatment plants design adopting genetic algorithm. The program was developed using Matlab software. The output of the genetic algorithm includes the finding of optimum design criteria for advanced wastewater treatment plants. The obtained design criteria are satisfying the required effluent quality with minimum treatment cost. Based on results of applying GA on ion exchange treatment plant, it was found that the optimum values of bed depth, service flowrate, regenerate flowrate, and back wash rate are 0.71m, 25m3/m3.hr, 8 m3/m3.hr, and 55 m/hr respectively.